Mathematical problem solving : Yearbook 2009, Association of Mathematics Educators - Kaur, Berinderjeet, 1955-; Yeap, Ban Har, 1968-; Kapur, Manu (World Scientific, 2009)
This book is the first in the series of the yearbooks of the Association of Mathematics Educators in Singapore. It is highly unique as it addresses a focused theme of mathematics education. The chapters of the book illustrate the immense diversity within the theme and presents research that translates into classroom pedagogies. The chapters of the book illustrate how mathematical problems may be crafted and infused in classroom teaching. Several novel pedagogies, such as learning mathematics through productive failure, problem posing and generative activities are presented in the book. The chapters are comprehensive and laden with evidence-based examples for both mathematics educators and classroom teachers of mathematics. The book is an invaluable contribution towards the already established field of research of mathematical problem solving. It is also a must read for graduate research students and mathematics educators.